Comparing consumption: a curse or a blessing? - Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
Does it make us unhappier when we compare our current consumption with that of the Joneses or our own past achievements? This paper tries an answer without recurring on interpersonal utility comparisons. It calibrates an economy under three different assumptions, non-comparing utility, and inward-looking and outward-looking habit formation. Using consumption equivalents it then calculates how much individual welfare is affected in each economy by unexpected losses and gains of wealth.
Keywords: D60; D91; E21; O40; 330; habit formation; happiness; welfare; economic growth; Konsumtheorie; Konsuminterdependenz; Vermögen; Lebenszufriedenheit; Wohlfahrtseffekt; Steady-State-Wachstum; Theorie